THE COMPUTER SUPPORT OF FUTURE NAVIGATORS’ OF “SEAWORTHY ASTRONOMY” - Sokol, I.B. (Journal of Information Technologies in Education (ITE), 2010)
In the given article the questions of computer support during the teaching of navigators on subject discipline “Seaworthy Astronomy” are considered at definition of calculated altitude and a luminary azimuth.